2002
DOI: 10.1353/dem.2002.0024
|View full text |Cite
|
Sign up to set email alerts
|

How well can we track cohabitation using the sipp? A consideration of direct and inferred measures

Abstract: Cohabitation is an alternative to marriage and to living independently for an increasing number of Americans. Despite this fact, research exploring links between living arrangements and economic behavior is limited by a lack of data that explicitly identify cohabiting couples. To aid researchers in using the Survey of Income and Program Participation's (SIPP) rich data for cohabitation issues, our paper considers direct and inferred measures of cohabitation. Our findings suggest that: (1) the best inferred mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…The past decline in the general marriage rate has been partially offset by a rise in nonmarital cohabitation. Recent studies have improved the measurement of cohabitation and indicate a larger increase than previously thought (Baughman, Dickert-Conlin, and Houser 2002;Casper and Cohen 2000). According to an analysis of the 1987-88 National Survey of Families and Households and the 1995 National Survey of Family Growth, the general cohabitation rate among women aged 15-29 increased from 2.1 percent in the early 1970s to 7.3 percent in the early 1990s and 12.3 percent in 2000, while the general marriage rate declined (Raley 2001).…”
Section: 3mentioning
confidence: 99%
“…The past decline in the general marriage rate has been partially offset by a rise in nonmarital cohabitation. Recent studies have improved the measurement of cohabitation and indicate a larger increase than previously thought (Baughman, Dickert-Conlin, and Houser 2002;Casper and Cohen 2000). According to an analysis of the 1987-88 National Survey of Families and Households and the 1995 National Survey of Family Growth, the general cohabitation rate among women aged 15-29 increased from 2.1 percent in the early 1970s to 7.3 percent in the early 1990s and 12.3 percent in 2000, while the general marriage rate declined (Raley 2001).…”
Section: 3mentioning
confidence: 99%
“…In the past, data was not explicitly collected on cohabiting partners precluding the possibility of accurately tracking cohabitation and more complex patterns such as those prevailing under transient domesticity (Baughman, Dickert-Conlin, & Houser, 2002; Casper & Cohen, 2000). This changed in 1990 when the Decennial Census added the option of specifying that a person was the unmarried partner of the householder, the person (or one of the persons) in whose name the home is owned or rented.…”
Section: Introductionmentioning
confidence: 99%
“…Because the CEX does not contain a direct measure of cohabitation, we rely upon an inferred measure. We follow Baughman, Dickert‐Conlin, and Houser (2002) by defining cohabiting‐parent families as those that contain both an unmarried family head and an unmarried and unrelated adult of the opposite gender. In addition, we require the age difference between these two family members to be 10 years or less.…”
Section: Introductionmentioning
confidence: 99%
“…Although this inferred measure will result in some degree of mismeasurement, several papers have found that inferred measures of cohabitation are reliable relative to direct measures (Baughman et al, 2002; Casper & Cohen, 2000; Manning, 1995 reported in Bauman, 1999). Any misclassification of cohabitation from using inferred measures will tend to lead to underestimates of any differences between cohabiting and other families.…”
Section: Introductionmentioning
confidence: 99%